Bcl-2 as a prognostic factor for survival in small-cell lung cancer - Ilievska Poposka, Biljana; Smichkoska, Snezhana; Crvenkova, Simonida; Zafirovska Ivanovska, B; Stefanovski, T; Petrusevska, G (Macedonian Academy of Sciences and Arts, 2008)
The expression of Bcl-2 oncoprotein is associated with inhibition of apoptosis and prolonged cell survival. The purpose of this study was to investigate Bcl-2 protein expression in patients with small-cell lung cancer (SCLC) in order to see if it was related to clinicopathological features and to prognosis.